Cognitive Tunneling in Obstetrics and Gynecology: A Critical Review of Implications for Clinical Practice and Mitigation Strategies - Dan Boitor; Mihai Surcel; Cristina Ioana Rotar; Gheorghe Cruciat; Georgiana Nemeti; Andreea Florian; Daniel Muresan; Mihaela Oancea (Diseases, 2026)
Cognitive tunnelling poses significant risks in OB/GYN, where rapid clinical deterioration and time-pressured decision-making are common. This critical review synthesized evidence from a comprehensive literature search across multiple databases, yielding 414 unique papers examining cognitive tunnelling mechanisms, patient safety consequences, and mitigation strategies in obstetric and gynecological contexts. Medicolegal analysis reveals that cognitive tunnelling contributes to malpractice exposure and that adoption of structured safety programs addresses root causes and strengthens the clinical record for forensic review. Mitigation strategies were critically evaluated: metacognition and individual cognitive forcing strategies such as DECLARE (Differential, Examine, Consider, List, Assess, Review, Evaluate) and Pivot-and-Cluster show theoretical promise but depend on intact executive capacity that is depleted under the very conditions that precipitate tunnelling; debriefing demonstrates consistent improvements in team situational awareness and latent threat identification but requires organizational just culture and psychological safety; and hierarchical closed-loop communication systems provide the strongest evidence of reducing preventable adverse events by distributing attentional load across teams, though authority gradients risk suppressing junior-staff dissent. Despite growing recognition, significant knowledge gaps remain regarding measurement methodologies, obstetric-specific research, intervention effectiveness, and the integration of emerging artificial intelligence technologies. Addressing cognitive tunneling through quality studies with patient-centered outcomes and validated measures is essential for reducing medical errors and enhancing patient safety in women’s healthcare.